A General Protocol for Radical Anion [3+2] Cycloaddition Enabled by Tandem Lewis Acid Photoredox Catalysis - Amador, Adrian G.; Sherbrook, Evan M.; Lu, Zhan; Yoon, Tehshik P. (Synthesis, 2018)
A method for intermolecular [3+2] cycloaddition between aryl cyclopropyl ketones and alkenes involving the combination of Lewis acid and photoredox catalysis is reported. In contrast to other more common methods for [3+2] cycloaddition, these conditions operate using a broad range of both electron-rich and electron-deficient reaction partners. The critical factors predicting the success of these reactions is the redox potential of the cyclopropyl ketone and the ability of the alkene to stabilize a key radical intermediate.
Keywords: cycloaddition; photoredox; photocatalysis; cyclopropane; cyclopentane